PROgesterone Therapy for Endometrial Cancer Prevention in Obese Women (PROTEC) Trial: A Feasibility Study. Issue 1 (January 2021) - Derbyshire, Abigail E.; Allen, Jennifer L.; Gittins, Matthew; Lakhiani, Bhavna; Bolton, James; Shaw, Joseph; Pemberton, Philip W.; Needham, Michelle; MacKintosh, Michelle L.; Edmondson, Richard J.; Kitchener, Henry C.; Crosbie, Emma J.
Abstract : (Abstracted from Cancer Prev Res (Phila) 2020; doi: 10.1158/1940-6207.CAPR-20-0248) Approximately 40% of endometrial cancers are thought to be directly attributable to obesity. The mechanism responsible for this association involves stimulation of the endometrium by adipose-derived estrogen unopposed by progesterone in anovulatory and postmenopausal women in addition to the effects of insulin resistance and chronic inflammation.